2022
DOI: 10.3389/fonc.2022.908956
|View full text |Cite
|
Sign up to set email alerts
|

New Diagnostic Model for Clinically Significant Prostate Cancer in Biopsy-Naïve Men With PIRADS 3

Abstract: PurposeThe aim of this study was to explore a new model of clinical decision-making to predict the occurrence of clinically significant prostate cancer (csPCa).Patients and MethodsThe demographic and clinical characteristics of 152 patients were recorded. Prostate-specific antigen (PSA), PSA density (PSAD), adjusted PSAD of peripheral zone (aPSADPZ), and peripheral zone volume ratio (PZ ratio) were calculated and subjected to receiver operating characteristic (ROC) curve analysis. The calibration and discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Within this subgroup of biopsy-positive men, 35.7% had clinically significant prostate cancer while 64.3% had indolent prostate cancer. Again, these results are similar to previous studies estimating a rate of 11-45% [ 14 - 18 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Within this subgroup of biopsy-positive men, 35.7% had clinically significant prostate cancer while 64.3% had indolent prostate cancer. Again, these results are similar to previous studies estimating a rate of 11-45% [ 14 - 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of mp-MRI scans reported as equivocal could be considered a surrogate marker of the MRI machine, imaging protocol, and radiologist experience. This study found that 21.6% of the total mp-MRI images were reported as Likert 3 prostate cancer; such a rate is comparable to other studies estimating 19-38.6% [7,14,16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation